Effect of Solvents in Synthesis of New 4-(2-hydroxy-5-methylphenyl)-5-aroyl-6-aryl-2-imino-6H-2,3-dihydro-1,3-thiazines - Dighade, S.R.; Chincholkar, M.M. (Asian Journal of Chemistry, 2010)
Seven different 3-aroylflavanones and 3-aroylchromanones were synthesised from 1,3-propanedione by literature method. They were subjected to react with different compounds such as (i) thiourea in pyridine. (ii) pyridine-KOH and (iii) ethanol-KOH medium to give respective 4-(2-hydroxy-5-methylphenyl)-5-aroyl-6-aryl-2-imino- 6H-2,3-dihydro 1,3-thiazines. The yield is better in case of pyridine- KOH.